Business process of garment accessories (zipper) supplier in Bangladesh : a study on NEO Zipper Company Ltd. - Rahman, Mohammad Mizanur (BRAC University, 2016)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Master of Business Administration, 2015.